CD49d associates with nodal presentation and subsequent development of lymphadenopathy in patients with chronic lymphocytic leukaemia. (7th April 2017) - Strati, Paolo; Parikh, Sameer A.; Chaffee, Kari G; Achenbach, Sara J.; Slager, Susan L.; Call, Timothy G.; Ding, Wei; Jelinek, Diane F.; Hanson, Curtis A.; Kay, Neil E.; Shanafelt, Tait D.
Summary: CD49d is a surface integrin that is expressed on chronic lymphocytic leukaemia (CLL) cells, and strongly correlates with more aggressive disease. Given its association with cell‐cell adhesion and leucocyte trafficking, we hypothesized that patients with high CD49d expression would experience a clinical course dominated by lymphadenopathy. CD49d expression was measured by flow cytometry and considered positive if expressed by ≥30% of CLL cells. The study included 797 newly diagnosed CLL/small lymphocytic leukaemia patients; 279 (35%) were CD49d positive. CD49d‐positive patients were more likely to present with lymphadenopathy ( P < 0·001); a finding that persisted after adjusting for fluorescence in situ hybridisation (FISH) and IGHV mutation status [odds ratio (OR) 2·51; 95% confidence interval (CI) 1·64–3·83; P < 0·001]. Among CLL Rai 0 patients, CD49d positivity was associated with shorter time to development of lymphadenopathy (3·2 years vs not reached, P < 0·01). This association was maintained after adjusting for either FISH [hazard ratio (HR) 2·18; 95% CI 1·25–3·81; P = 0·006) or IGHV status (HR 2·02; 95% CI 1·11–3·69; P = 0·02) individually, but was attenuated when adjusting by both (HR 1·72; 95% CI 0·88–3·38; P = 0·11).These data demonstrate that CD49d‐positive CLL patients experience a disease course dominated by lymphadenopathy. These findings could have implications for therapy selection and disease monitoring.